Phos, Our Other Greek Name - Haas, Andrew (Sophia, 2021)
It is perhaps time to revivify our other name in Greek: phos. For although the Greeks named us anthrôpos, they also called us phos. And the Greeks used the word phos because we are like light. Indeed, our way of being light-like is illuminating, which illuminates being and the truth of being, so that it can be thought and said, imagined, and sensed—especially insofar as we are this illumination. Thus, it is time to reclaim phos as our name and so rethink what it means to illuminate, whether we light up everything that is (and is not), as well as ourselves, or not.